2014
DOI: 10.1088/1475-7516/2014/11/002
|View full text |Cite
|
Sign up to set email alerts
|

Excluding the light dark matter window of a 331 model using LHC and direct dark matter detection data

Abstract: We sift the impact of the recent Higgs precise measurements, and recent dark matter direct detection results, on the dark sector of an electroweak extension of the Standard Model that has a complex scalar as dark matter. We find that in this model the Higgs decays with a large branching ratio into dark matter particles, and charged scalars when these are kinematically available, for any coupling strength differently from the so called Higgs portal. Moreover, we compute the abundance and spin-independent WIMP-n… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
58
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 65 publications
(60 citation statements)
references
References 162 publications
2
58
0
Order By: Relevance
“…(vi) These models contain a natural Peccei-Quinn symmetry, which solves the strong-CP problem [111][112][113][114]. (vii) The 3-3-1 models with heavy sterile neutrinos include cold dark matter candidates as weakly interacting massive particles (WIMPs) [115][116][117][118]. A concise review of WIMPs in 3-3-1 Electroweak Gauge Models is provided in ref.…”
Section: Introductionmentioning
confidence: 99%
“…(vi) These models contain a natural Peccei-Quinn symmetry, which solves the strong-CP problem [111][112][113][114]. (vii) The 3-3-1 models with heavy sterile neutrinos include cold dark matter candidates as weakly interacting massive particles (WIMPs) [115][116][117][118]. A concise review of WIMPs in 3-3-1 Electroweak Gauge Models is provided in ref.…”
Section: Introductionmentioning
confidence: 99%
“…TeV, which contrasted with recent LUX results on direct detection (Akerib et al, 2014), implies a lower bound to φ mass, 500 m φ > ɶ GeV (Cogollo et al, 2014), as can be seen in Fig. 3.…”
Section: Wimp In 331lhnmentioning
confidence: 64%
“…This explanation fits well in the context of 331LHN model, since the lightest heavy neutral fermion, N 1 , can play the role of the mother particle, decaying into φ plus an active neutrino with parameters appropriate to produce only a fraction of relativistic WIMPs, remarking that this fraction must not exceed 0:01% of the whole number of WIMPs so as to not jeopardize structure formation (Hooper et al, 2012). This approach was followed in (Kelso et al, 2014) and has been shown to be feasible for the 331LHN model while keeping consistency with the above mentioned constraints on GeV (Cogollo et al, 2014).…”
Section: Wimp In 331lhnmentioning
confidence: 94%
See 1 more Smart Citation
“…The leptoquarks possessing B = -1 as we put are in order to cancel the baryonic anomalies. Note that in the framework of the 3-3-1 models, the family number achieved has a different origin, which is a consequence of the new weak-isospin symmetry SU(3) L with a corresponding enlargement of the lepton and quark representations (see, for recent works, Kelso et al, 2014;Cogollo et al, 2014;Dong et al, 2014;2012). It is noteworthy that the [SU(2)] 2 U(1) Y anomaly was removed because of Y(F L ) = 0 and this is why we assumed q j = -q k = 1/2.…”
Section: The Modelmentioning
confidence: 99%